2017
DOI: 10.1016/j.canlet.2016.10.011
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA and gene co-expression networks characterize biological and clinical behavior of rhabdomyosarcomas

Abstract: Rhabdomyosarcomas (RMS) in children and adolescents are heterogeneous sarcomas broadly defined by skeletal muscle features and the presence/absence of PAX3/7-FOXO1 fusion genes. MicroRNAs are small non-coding RNAs that regulate gene expression in a cell context specific manner. Sequencing analyses of microRNAs in 64 RMS revealed expression patterns separating skeletal muscle, fusion gene positive and negative RMS. Integration with parallel gene expression data assigned biological functions to 12 co-expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 55 publications
6
15
0
Order By: Relevance
“…MiR-221 is significantly reduced in FP-RMS compared to FN-RMS (Fig. 4a ) consistent with a recent study in 64 RMS patients [ 31 ]. Transient transfection of miR-221 mimic led to overexpression as evaluated by qRT-PCR, reduction of cell viability, and an increase in apoptosis in both Rh30 and Rh41 cells (Fig.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…MiR-221 is significantly reduced in FP-RMS compared to FN-RMS (Fig. 4a ) consistent with a recent study in 64 RMS patients [ 31 ]. Transient transfection of miR-221 mimic led to overexpression as evaluated by qRT-PCR, reduction of cell viability, and an increase in apoptosis in both Rh30 and Rh41 cells (Fig.…”
Section: Resultssupporting
confidence: 91%
“…In endothelial cells, miR-221/222 inhibit proliferation, migration, and angiogenesis [ 49 ]. Consistent with our findings, miR-221/222 are downregulated specifically in FP-RMS cell lines and patients [ 31 , 50 ]. Interestingly miR-221/222 expression correlates with overall survival and progression-free survival of RMS [ 31 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous studies have reported that miR-9-5p is ectopically regulated in various types of cancers. miR-9-5p levels are higher in metastatic tumors compared with non-metastatic tumors and these were demonstrated to be associated with poor prognosis of rhabdomyosarcomas (44). The homeotic gene miR-9 inhibited ovarian cancer cell growth via nuclear factor-κβ1 (45).…”
Section: Discussionmentioning
confidence: 99%
“…They discovered that FILNC1 represses c‐Myc‐mediated energy metabolism and inhibits renal tumor development . Additionally, studies have also demonstrated that FOXO1 has antitumor actions in spindle cell lipoma, rhabdomyosarcomas and Kaposi's sarcoma (Table ).…”
Section: Roles Of Foxo1 In Diverse Human Neoplasmsmentioning
confidence: 99%